Role of Alanine Aminotransferase in Determining the Biliary Etiology in Acute Pancreatitis - Bharti, Shiv Vansh; Sharma, Anup (Journal of Nepalgunj Medical College, 2021)
Introduction: Acute pancreatitis a disorder that has numerous causes and an obscure pathogenesis. It can be a serious abdominal emergency associated with significant morbidity and mortality. Cholelithiasis is most common cause of acute pancreatitis and excessive alcohol consumption is second most frequent cause which together account for approximately 80% of underlying etiology. The detection of biliary etiology is crucial to delivery of definitive therapy to prevent repeated attacks of acute pancreatitis. During an attack of acute pancreatitis, elevation of alanine aminotransferase to >150 IU/L is a predictive factor for biliary cause of acute pancreatitis. Aims: To investigate the predictive value of raised alanine aminotransferase in determining biliary etiology in patients presenting with acute pancreatitis. Methods: A prospective study was done among 70 patients who were admitted in surgery department over a period of one year with diagnosis of acute pancreatitis. Peak alanine aminotransferase within 48 hours of presentation was recorded. The diagnosis was based on typical clinical presentation of acute pancreatitis combined with an increase in serum amylase levels ≥ 3 times the upper limit of the laboratory reference value. All biliary cases were confirmed by abdominal ultrasonography. Results: The mean age of the patients was 47.9 ±15.7 years (19-88 years). Acute pancreatitis was common in 31-40 years of age group. Among them, 40(57.1%) were male and 30(42.9%) were female. Forty two (60%) patients had biliary pancreatitis, 20(28.5%) had alcoholic pancreatitis, 2(2.8%) patients had drug induced pancreatitis and 6(8.5%) patients had idiopathic pancreatitis. Mean alanine aminotransferase for biliary pancreatitis was 205.9U/L, while cases with other etiologies (alcoholic 58.4U/L; drug induced 62.6 U/L; and idiopathic 48.3 U/L) showed significantly lower values (p=0.001). Conclusion: An elevated alanine aminotransferase strongly supports a diagnosis of gallstones in acute pancreatitis.